2018
DOI: 10.13075/mp.5893.00675
|View full text |Cite
|
Sign up to set email alerts
|

Spine arrangement during work in sitting position and occurrence of pain among dentists and medical assistants

Abstract: StreszczenieWstęp: Ból kręgosłupa często występuje u osób pracujących w pozycji siedzącej. Na jakość tej pozycji ma wpływ m.in. rodzaj stanowiska roboczego. Dla stomatologów stanowiskami roboczymi są unity stomatologiczne, konstruowane na podstawie współcze-snych ergonomicznych koncepcji pracy, natomiast asystenci medyczni pracują na typowych komputerowych stanowiskach biurowych. Celem badania było określenie zależności między dolegliwościami bólowymi a ustawieniem kręgosłupa podczas pracy w pozycji siedzącej … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In the study group, a greater range of movements was also observed to the right side compared to the left side and this may be closely related to the nature of the space occupied at the dental unit. Similarly, Nowotny-Czupryn et al report that assistants were more likely to work with the cervical segment rotated more to one side than the dentist herself: 57.5% more often to the right and 42.5% more often to the left [15].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the study group, a greater range of movements was also observed to the right side compared to the left side and this may be closely related to the nature of the space occupied at the dental unit. Similarly, Nowotny-Czupryn et al report that assistants were more likely to work with the cervical segment rotated more to one side than the dentist herself: 57.5% more often to the right and 42.5% more often to the left [15].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Nowotny-Czupryn et al . report that assistants were more likely to work with the cervical segment rotated more to one side than the dentist herself: 57.5% more often to the right and 42.5% more often to the left [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our examination showed that working hours are an important risk factor for pain occurrence. Some examinations show (8)(9)(10)(11) that most of the teaching personnel who take the sitting position have kyphotic posture. Ergonomically looking, the teaching personnel should take positions which preserve the physiological curves of the spine.…”
Section: Discussionmentioning
confidence: 99%